the Hubungan antara Kepuasan dengan Loyalitas Pelanggan di Apotek Olivia Jakarta Utara Bulan Desember 2024 - Handono, Bayu Dwi; Brahmono, Umul Angga; Yoyoh, Yoyoh (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
The increasing number of pharmacies in recent years has intensified competitive complexity within the pharmaceutical sector, particularly in the context of the digital era, which enables the public to easily access comparative information about products and services across healthcare institutions. In the framework of high-quality healthcare services, customer satisfaction serves as a critical indicator reflecting the extent to which service quality meets user expectations. According to service management literature, there is a significant influence of customer satisfaction on loyalty, where individuals who perceive value aligned with their expectations are more likely to exhibit repetitive purchasing behavior and social recommendations over the long term. Therefore, enhancing service value and quality constitutes a key factor in fostering sustainable customer relationships. The present study was carried out to explore the relationship between customer satisfaction and loyalty within the context of Olivia Pharmacy, North Jakarta. A quantitative descriptive approach was employed, utilizing simple random sampling to select 314 respondents as participants. Statistical analysis indicated a correlation coefficient of 0.596, with a p-value of 0.000 (p < 0.01), suggesting a moderate yet statistically significant positive association between the variables under investigation. These supports the hypothesis that higher levels of customer satisfaction positively influence customer loyalty. The study concludes that customer satisfaction is not an isolated variable, but rather a strategic component that forms a foundational element in decision-making for service improvement programs. By systematically focusing on comprehensive enhancements in service quality, Olivia Pharmacy can strategically build long-term customer loyalty, transforming it into a sustainable competitive advantage amid increasingly intense market competition.